PEMBELAJARAN DENGAN KECERDASAN JAMAK DI SEKOLAH - Asep Kurniawan (Al Ibtida: Jurnal Pendidikan Guru MI, 2015)
Traditional assumption, which has been adopted in education, will be difficult to produce highly qualified graduates. A big mistake if student achievement is measured only by the ability of IQ in the form of mathematics and language. A great misconceptions if student achievement is only measured by the ability of IQ (Intelligence Quotient); mathematics and language. Intelligence IQ in favor of only a small portion of the learners. Intelligence is not only IQ, but also multiple intelligencies, such as Linguistic Intelligence, Logical-Mathematical Intelligence, Spatial-Visual Intelligence, Bodily-Kinesthetic Intelligence, Musical Intelligence, Interpersonal Intelligence, Intrapersonal Intelligence, Naturalist Intelligence, Existential Intelligence, and Spiritual Intelligence. It is based on the understanding of intelligence as the ability of a person to solve a real problem and in a variety of situations. In the context of learning in school, multiple intelligences actualized by empowering learners, more than one modality of learning, variation of places, which is very important, appropriateness teacher's teaching style with students’ learning styles, or students’ intelligences. Learning with multiple intelligences will be able to connect the tedious learning process to a joyful learning. Students are not crammed full of material and theories. With this, however, students are faced with the reality that the material and theories can indeed they encounter in their daily lives, thereby providing the depth impression.  Key words: Pembelajaran, inovasi, kecerdasan, Jamak.